2013
DOI: 10.4236/wja.2013.33027
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Candida Species Isolated from Cases of Lower Respiratory Tract Infection among HIV/AIDS Patients in Calabar, Nigeria

Abstract: This study was designed to identify and characterize the Candida species isolated from lower respiratory tract infections among HIV positive patients and to determine the prevalence rates of Candida infections among these subjects. Two early morning expectorate sputum samples were collected from 272 HIV positive subjects visiting the ART clinics and DOTS centre with cases of lower respiratory tract infection, over a period of 14 months from May 2009 to July 2010 in Calabar. Subjects were recruited for this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 4 publications
1
14
1
Order By: Relevance
“…Lymphopenia was observed in about 20% of the study participants which was similar to a report by Ogba et al (2013). About 5% of the study participants had neutropenia and are hence at great risk of developing infections at different sites including the skin, mucosa and the lungs (Boxer, 2012).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Lymphopenia was observed in about 20% of the study participants which was similar to a report by Ogba et al (2013). About 5% of the study participants had neutropenia and are hence at great risk of developing infections at different sites including the skin, mucosa and the lungs (Boxer, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…as strong predictors of mortality and morbidity in HIV infected patients (Shen et al, 2013).Hematological complications among HIV are generally marked with cytopenias such as anemia, thrombocytopenia, leucopenia, and lymphopenia.The occurrence and severity of the cytopenias normally correlate with the stage of disease (Ogba et al, 2013).…”
Section: Hematological Abnormalities Have Been Documentedmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies showed the regular detection of Candida species in sputa of patients with lower respiratory tract infection, cystic fibrosis, pulmonary tuberculosis and HIV infected patients. [5][6][7][8][9] High isolation rate for Candida species from sputum samples were reported from patients at the age above 50 year in Nepal and India. 23,24 These results are in a agreement with our finding.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies dealt with the identification and characterized Candida species isolated from sputum in HIV positive patients [5][6][7] and from pulmonary tuberculosis patients. 8,9 In Iraq, however, eight Candida species namely C. albicans, C. curvata, C. glabrata, C. kefyr, C. krusei, C. paropsiloses, C. tropicalis and C. utilis were detected in sputa of patients with pulmonary tuberculosis in Basrah, Iraq.…”
mentioning
confidence: 99%